Promoting Underrepresented Minority Student Academic Success Using an Inclusive Faculty Framework - Don Gillian-Daniel; Sean Thomas Bridgen; Wendy Troxel (Academic Chairpersons Conference Proceedings, 2022)
The Aspire Alliance has developed the Inclusive Faculty Framework (IFF), which is grounded in research and theory, and engages faculty in the development of foundational skills that promote increased student academic success. This workshop will present the IFF, and use the underlying principles to engage participants in the development of foundational skills that promote increased success of students, particularly those from underrepresented groups. Participants will experience a range of activities including, and not limited to, discussions, case-based scenarios, as well as individual and group reflection
Keywords: Inclusivity Equity Teaching Advising Faculty